Testing for language teachers - Hughes, Arthur 1941- (Cambridge University Press, 2003)
This second edition remains the most practical guide for teachers who want to have a better understanding of the role of testing in language teaching. It has a new chapter on testing young learners and expanded chapters on common test techniques and testing overall ability
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Sprache; Language and languages / Ability testing; Language and languages / Study and teaching; Language teachers / Training of; Sprachtest; Neusprachlicher Unterricht; Englischunterricht